Mechanism of Microwave Assisted Hydrodistillation Studied Through Heat Analysis - Nitthiyah, Jeyaratnam; Nour, A. H.; K., Ramesh; Akindoyo, John Olabode (Universiti Malaysia Pahang, 2016)
In this study, the efficiency of heating mechanism of microwave assisted hydrodistillation (MAHD) in the extraction of cinnamon bark oil was investigated. The optimum conditions used to analyse the heating performance were 8:1 ratio of water to cinnamon bark powder and fixed 250 W of irradiation power. The increasing temperature in the cinnamon bark matrix was dependent on the solvent, physical, dielectric and heating properties of the cinnamon matrix. Due to the high dielectric properties of water it accelerated the process of extraction. However, after the cinnamon matrix reached the boiling point, the density of solvent decreased which led to decrease in the dielectric properties. Volume rate of heat generation and penetration depth of microwave was also evaluated. The rate of volume heat generation reduced when the exposure time increase which is related to the reducing dielectric properties of cinnamon matrix. The penetration depth was calculated to support the data of dielectric properties. This study therefore produced an in depth justification necessary to understand the heating mechanism of MAHD in extraction of cinnamon bark essential oil.